A Comparison Between Certain English and Cer¬tain American Blast Furnaces, as to their Capacity, by Measurement and their Capacity by Weight - Frank Firmstone (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1873)
IN Chemical Phenomena of Iron Smelting, Mr. Bell gives the weight of materials required to fill furnaces of various sizes at the Clarence Works ; as this differs very much from the weight required for furnaces at Glendon, where anthracite and magnetic and brown iron-ores are used, a comparison is interesting. Taking furnaces at Glendon of 4800 and 11,900 cubic feet capacity and comparing them with the Clarence furnaces of 6000 cubic feet and 11,500 cubic feet, we find that the 4800 cubic feet at Glendon and the 6000 cubic feet at Clarence required respectively-